2010
DOI: 10.1016/j.crvi.2010.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Studying sources of incongruence in arthropod molecular phylogenies: Sea spiders (Pycnogonida) as a case study

Abstract: This study; 1 [1]; 2 [16]; 3 [17]. **Species not included at first in the multi-marker analyses. MNHN: specimen and DNA preserved in the collection of UMR 7205 (MNHN). Chimera used for outgroup taxa: a L. variegatus; b L. sp.; c L. obscurus; d L. forficatus; e Orthoporus sp.; f Unixenus mjobergi; g Thyropygus sp.; h Squilla empusa; i Kempina mikado; j T. longicaudatus; k T. sp.; l T. australiensis; m Locusta migratoria; n Gomphocerinae sp.; o Tenebrio molitor; p Tenebrio sp.; q Tribolium castaneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 51 publications
2
53
1
Order By: Relevance
“…Both palpal and ovigeral basal parts seems to have undergone similar patterns of evolution. According to the described palpal and ovigeral article reduction in the three basal-most extant families in Pycnogonida: Austrodecidae, Pycnogonidae, and Colossendeidae [2,5], the Colossendeiidae retain the primitive form of palp and oviger ( [4]: 305), with similar expression in males and females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both palpal and ovigeral basal parts seems to have undergone similar patterns of evolution. According to the described palpal and ovigeral article reduction in the three basal-most extant families in Pycnogonida: Austrodecidae, Pycnogonidae, and Colossendeidae [2,5], the Colossendeiidae retain the primitive form of palp and oviger ( [4]: 305), with similar expression in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Some contributions based on molecular data suggested that the Austrodecidae (the only family included in Stiripasterida) is the basal-most group, being the sister group of the remaining extant families (all them in Eupantopodida) [2,5]. In this last clade, including 95 % of the extant pycnogonids species, the families Pycnogonidae and Colossendeidae are the basal-most groupings.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the three markers (18S, 28S, and CO1) was amplified and sequenced using the primers employed in previous studies (Arabi et al 2010;Hassanin et al 2005), plus three new specific primers for the 28S (R4S: 5 0 -GAAGACCCTGTTGAGCTTGACT-3 0 /R4AS: 5 0 -GATTCTGACTTAGAGGCGTTCA-3 0 ) and CO1 (U1sco: 5 0 -TCWACDAATCATAAGGATATTGGDAC-3 0 ). PCR reactions were carried out in a 30-ll final volume using the following conditions: 109 reaction buffer with MgCl 2 , 3 ll; dNTP mix (6.6 mM), 3 ll; primers (10 lM), 1.5 ll; H 2 O, 19.3 ll; Sigma Red Taq DNA polymerase, 0.70 ll, and DNA template, 1 ll.…”
Section: Extraction Pcr and Sequencingmentioning
confidence: 99%
“…More specifically, Chelicerata can be divided into 12 orders: Pantopoda (Pycnogonida), Xiphosura (Merostomata), and the Arachnida orders Acari, Amblypygi, Araneae, Opiliones, Palpigradi, Pseudoscorpiones, Ricinulei, Scorpiones, Solifugae, and Uropygi (Shultz 2007;Weygoldt and Paulus 1979). In this report, we focused on the subphylum Chelicerata because previous studies have shown that several unrelated taxa in this clade have a mtDNA characterized by a global reversal of strand compositional bias, including one sea spider (Achelia bituberculata : Arabi et al 2010), opisthothele spiders (Argiope, Caligosa, Habronattus, Hypochylus, Nephila, and Ornithoctonus), scorpions (Buthus, Centruroides, Euscorpius, Mesobuthus, and Uroctonus) (Hassanin 2006;Hassanin et al 2005;Masta et al 2009), and two unrelated species of mites (Varroa destructor : Hassanin 2006 and Steganacarus magnus: Domes et al 2008). These observations suggest that many mitogenomic inversions occurred during the evolutionary history of Chelicerata.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation